Fundamental concepts and models for the direct problem - Jorge, Ariosto Bretanha (ed.) (2022)
This book series is an initiative of the Post Graduate Program in Integrity of Engineering Materials from UnB, organized as a collaborative work involving researchers, engineers, scholars, from several institutions, universities, industry, recognized both nationally and internationally. The book chapters discuss several direct methods, inverse methods and uncertainty models available for model-based and signal based inverse problems, including discrete numerical methods for continuum mechanics (Finite Element Method, Boundary Element Method, Mesh-Free Method, Wavelet Method). The different topics covered include aspects related to multiscale modeling, multiphysics modeling, inverse methods (Optimization, Identification, Artificial Intelligence and Data Science), Uncertainty Modeling (Probabilistic Methods, Uncertainty Quantification, Risk & Reliability), Model Validation and Verification. Each book includes an initial chapter with a presentation of the book chapters included in the volume, and their connection and relationship with regard to the whole setting of methods and models.